GO/glucose/PEDOT:PSS ternary nanocomposites for flexible supercapacitors. (1st September 2018) - Giuri, Antonella; Colella, Silvia; Listorti, Andrea; Rizzo, Aurora; Mele, Claudio; Corcione, Carola Esposito
Abstract: Poly (3, 4 ethylenedioxythiophene)polystyrene sulfonate (PEDOT:PSS), among the most used conductive polymers, shows properties easily modulating by adding fillers as Graphene Oxide (GO). Recently, PEDOT-based polymers have been used with encouraging results as electrodes for flexible supercapacitors. We have already developed a green ternary nanocomposite based on PEDOT:PSS doped with GO and glucose (GGO-PEDOT) with a specific capacitance of 16 F/g, indicating how this nanocomposite is potentially suitable to be used as an electrode material for a supercapacitor. In this work, a free-standing nanocomposite film was realized by drop casting the solution in a proper silicone mould, followed by peeling and thermal annealing. Specific analyses, such as thermogravimetric, colorimetric and contact angle measurements, have been performed aiming at assessing the stability of the thermal and of the surface properties, even in severe moisture and UV aging conditions. Finally, The capacitive performance of PEDOT:PSS and of GGO-PEDOT was investigated by means of cyclic voltammetry (CV), in the pristine conditions and under UV aging. The deposited GGO-PEDOT film showed a good conductive behaviour and stability under UV treatment of 4 h.